Ксенотрансплантація мікроінкапсульованої тканини аденоми прищитоподібної залози людини (експериментальне дослідження) - Пастер, І. П.; Балла, І. А. (Clinical Endocrinology and Endocrine Surgery, 2009)
Xenotransplant of the microencapsulated human parathyroid adenoma tissue preserves the high viability and the ability to secrete parathormone, and have marked positive effect on the levels of total and free calcium in rat recipient blood with experimental hypoparathyroidism, which suggests good prospects of using this tissue in the presence of compensated hypofunctional state of parathyroid system in clinical practice.